Magnetostriction in the mixed state of superconducting 2H-NbSe2 single crystals - Eremenko, V. V.; Sirenko, V. A.; Schleser, R.; Gammel, P. L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Magnetostriction measurements on 2H-NbSe2 single crystals in the temperature range 1.5-8 K in a magnetic field up to 14 T are reported. Peak and oscillations in the measured field dependences ofmagnetostriction were observed near Hc2. The reversible and irreversible components are separated andanalyzed in the region of peak. The scaling parameters are defined, the contribution of the elastic constants dependence on magnetic field is demonstrated. The oscillatory component is discussed regarding Landau quantization of electronic spectrum.